From hope to alert: demography of a remnant population of the Critically Endangered Atelopus varius from Costa Rica. (2nd September 2018) - González-Maya, José F.; Gómez-Hoyos, Diego A.; Cruz-Lizano, Ivan; Schipper, Jan
ABSTRACT: Harlequin frogs have suffered severe declines across the Neotropics. We present a population assessment for a recently discovered population of Atelopus varius from Costa Rica. Using mark-recapture methods from September 2011 to February 2013, we estimated survival and recruitments parameters using Cormack-Jolly-Seber models. We obtained 222 captures and estimated low recruitment rates and high seniority. Given estimates of population growth rates close to zero, the observed population seems to be stable during the study. However, contrary to expectations for seasonally reproducing species like A. varius, we did not find an increase in recruitment rates between dry and rainy season. We provide details on ongoing threats for the population, as well as propose conservation actions to mitigate these threats.